2021
DOI: 10.1111/jfbc.13964
|View full text |Cite
|
Sign up to set email alerts
|

Sialoglycoproteins isolated from the eggs of Carassius auratus alleviates CCL4‐induced liver injury via downregulation of the IRE‐α/NF‐κB signaling pathway

Abstract: Chemical liver injury is a common cause of liver disease primarily characterized by oxidative stress and inflammation. Sialoglycoproteins isolated from the eggs of Carassius auratus (Ca‐SGP) have been proved to exhibit the antioxidant effect. However, the effect of Ca‐SGP on liver injury remains unclear. Thus, this study was aimed to determine the effect of Ca‐SGP on CCL4‐induced chronic chemical liver injury and explore the underlying molecular mechanism. Results showed that Ca‐SGP mitigated the elevated leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested that inflammation plays an important role in the pathogenesis and progression of CCl 4 -induced liver damage [ 28 ]. Kupffer cells, as resident hepatic macrophages, are activated by oxidative stress to release inflammatory factors (TNF-α, IL-6, and IL-1β) that aggravate liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that inflammation plays an important role in the pathogenesis and progression of CCl 4 -induced liver damage [ 28 ]. Kupffer cells, as resident hepatic macrophages, are activated by oxidative stress to release inflammatory factors (TNF-α, IL-6, and IL-1β) that aggravate liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, salivary glycoprotein from Carassius auratus alleviated drug-induced liver injury via inhibiting the expression of endoplasmic reticulum stress-related proteins. 9 However, more natural products still need to be explored.…”
Section: Introductionmentioning
confidence: 99%